Inhibition of delta-protein kinase C by delcasertib as an adjunct to primary percutaneous coronary intervention for acute anterior ST-segment elevation myocardial infarction: results of the PROTECTION AMI Randomized Controlled Trial - Lincoff, A Michael; Roe, Matthew; Aylward, Philip; Galla, John; Rynkiewicz, Andrzej; Guetta, Victor; Zelizko, Michael; Kleiman, Neal; White, Harvey; McErlean, Ellen; Erlinge, David; Laine, Mika; et al. (European heart journal, 2014)
AIMS: Delcasertib is a selective inhibitor of delta-protein kinase C (delta-PKC), which reduced infarct size during ischaemia/reperfusion in animal models and diminished myocardial necrosis and improved reperfusion in a pilot study during primary percutaneous coronary intervention (PCI) for ST elevation myocardial infarction (STEMI). METHODS AND RESULTS: A multicentre, double-blind trial was performed in patients presenting within 6 h and undergoing primary PCI for anterior (the primary analysis cohort, n = 1010 patients) or inferior (an exploratory cohort, capped at 166 patients) STEMI. Patients with anterior STEMI were randomized to placebo or one of three doses of delcasertib (50, 150, or 450 mg/h) by intravenous infusion initiated before PCI and continued for ∼2.5 h. There were no differences between treatment groups in the primary efficacy endpoint of infarct size measured by creatine kinase MB fraction area under the curve (AUC) (median 5156, 5043, 4419, and 5253 ng h/mL in the placebo, delcasertib 50, 150, and 450 mg/mL groups, respectively) in the anterior STEMI cohort. No treatment-related differences were seen in secondary endpoints of infarct size, electrocardiographic ST-segment recovery AUC or time to stable ST recovery, or left ventricular ejection fraction at 3 months. No differences in rates of adjudicated clinical endpoints (death, heart failure, or serious ventricular arrhythmias) were observed. CONCLUSIONS: Selective inhibition of delta-PKC with intravenous infusion of delcasertib during PCI for acute STEMI in a population of patients treated according to contemporary standard of care did not reduce biomarkers of myocardial injury.
Keywords: Humans; inhibitory proteinkinas; lidé středního věku; Myocardial; koronární angioplastika; Double-Blind Method; Chemotherapy, Adjuvant; Drug Administration Schedule; Pharmacology; Female; Aged; Area Under Curve; Stunning; výsledek terapie; senioři; dvojitá slepá metoda; lidé; Biomarkers; infarkt myokardu; kreatinkinasa, forma MB; peptidy; adjuvantní chemoterapie; pilotní projekty; Pilot Projects; Peptides; Troponin I; Protein Kinase Inhibitors; Reperfusion; Stents; biologické markery; ženské pohlaví; Male; Middle Aged; Myocardial Infarction; Treatment Outcome; Myocardial infarction; Infusions, Intravenous; troponin I; Percutaneous Coronary Intervention; plocha pod křivkou; Creatine Kinase, MB Form; mužské pohlaví; intravenózní infuze; rozvrh dávkování léků